A coupled SPH-DEM model for fluid-structure interaction problems with free-surface flow and structural failure. (December 2016) - Wu, Ke; Yang, Dongmin; Wright, Nigel
Highlights: An integrated SPH-DEM particle model for fluid-structure interaction (FSI) problems. Structural deformation and failure is modelled by DEM through bonded particles. Free surface flow is modelled by SPH based on the kernel and particle approximations. The SPH-DEM model is validated against other methods for FSI problems without fracture. The capability of SPH-DEM modelling of fluid induced structural failure is demonstrated. Abstract: An integrated particle model is developed to study fluid-structure interaction (FSI) problems with fracture in the structure induced by the free surface flow of the fluid. In this model, the Smoothed Particle Hydrodynamics (SPH) based on the kernel approximation and particle approximation is used to model the fluid domain in accordance with Navier-Stokes equations and the Discrete Element Method (DEM) with a parallel bond model is used to represent the real solid structure through a hexagonal packing of bonded particles. Validation tests have been carried out for the DEM model of the structure with deformation and fracture failure, the SPH model of the fluid and the coupled SPH-DEM model of FSI without fracture, all showing very good agreement with analytical solutions and/or published experimental and numerical results. The simulation results of FSI with fracture indicate that the SPH-DEM model developed is capable of capturing the entire FSI process from structural deformation to structural failure and eventually to post-failure deformable body movement.